2021
DOI: 10.1002/anie.202111700
|View full text |Cite
|
Sign up to set email alerts
|

Highly Ethylene‐Selective Electrocatalytic CO2 Reduction Enabled by Isolated Cu−S Motifs in Metal–Organic Framework Based Precatalysts

Abstract: Copper-based materials are efficient electrocatalysts for the conversion of CO 2 to C 2+ products,a nd most these materials are reconstructed in situ to regenerate active species. It is achallenge to precisely design precatalysts to obtain active sites for the CO 2 reduction reaction (CO 2 RR). Herein, we develop astrategy based on local sulfur doping of aCu-based metal-organic framework precatalyst, in whichthe stable CuÀ Smotif is dispersed in the framework of HKUST-1 (S-HKUST-1). The precatalyst exhibits ah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(46 citation statements)
references
References 74 publications
3
43
0
Order By: Relevance
“…For HKUST-1 and HKUST-1-nC-Zn samples, the peak wavenumbers of FT-IR at these positions were nearly identical, demonstrating that the MOF framework maintained the versatile integrity of the organic−inorganic hybrid structure after ALI infiltration. 32,51 Additionally, the water-coordinated Cu feature at 1550 cm −1 in HKUST-1 decreased in intensity with the increase of ALI cycles. 52 This phenomenon was consistent with the observed color change of HKUST-1, indicating that the introduction of Zn gradually removed coordinated water molecules and impeded the coordination of other water molecules.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…For HKUST-1 and HKUST-1-nC-Zn samples, the peak wavenumbers of FT-IR at these positions were nearly identical, demonstrating that the MOF framework maintained the versatile integrity of the organic−inorganic hybrid structure after ALI infiltration. 32,51 Additionally, the water-coordinated Cu feature at 1550 cm −1 in HKUST-1 decreased in intensity with the increase of ALI cycles. 52 This phenomenon was consistent with the observed color change of HKUST-1, indicating that the introduction of Zn gradually removed coordinated water molecules and impeded the coordination of other water molecules.…”
Section: Resultsmentioning
confidence: 96%
“…This could be due to generated Zn−O species occupying the cavity of HKUST-1 and lowering the pore cage, leading to a modest decrease in specific surface area, which also indicated that the successful assembly of the Zn−O clusters with the HKUST-1 framework retained the structural integrity. 32 An ICP-OES analysis was performed in order to quantify the Cu and Zn elements in the HKUST-1 and ALImodified HKUST-1 samples, as shown in Table S2. With an increase in the number of deposition cycles, the content of Zn atoms also increased, and the ratio of Cu to Zn atomic content relatively decreased.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wen et al created a technique based on local sulfur doping of a Cu-based MOF pre-catalyst, in which the stable Cu-S motif is spread throughout the HKUST-1 framework (S-HKUST-1) [44]. The precatalyst can be reassembled in situ in the flow cell to provide a Cu(S) matrix with active biphasic copper/copper sulfide interfaces, delivering a current density of 400 mA cm -2 and a high FE of C 2 H 4 (up to 57.2 %).…”
Section: Productsmentioning
confidence: 99%